Global Supply Chain Security: Emerging Topics in Research, Practice and Policy - Thomas, Andrew R (Springer, 2015)
This volume presents new theoretical insights, practical strategies, and policy initiatives in the rapidly evolving field of global supply chain security. As businesses, governments, and society at large have become increasingly dependent on a global network to provide goods and services, protecting global supply chains has become an issue of vital importance for industries, nations, and regions. The "supply chain" encompasses all the links connecting a manufacturer to end users of its products. Links may take the form of plants, supplier warehouses, vendor facilities, ports or hubs, retail warehouses or facilities, and outbound shipping centers. Links also involve all the ways goods are moved-by truck, ship, airplane, or rail car.